Epigraphic form, from Ann Radcliffe to George Eliot - Yem, E (2020)
My thesis charts a history of the chapter epigraph through the eighteenth-century periodical, and the novels of Ann Radcliffe, Walter Scott, and George Eliot. It examines the formal developments and stylistic variations of epigraph composition practiced by these authors, shedding light on the content and aims of their fiction, and on how they sought to moderate the imagined relationship between reader and writer. I argue that while Radcliffe, Scott, and Eliot, used the epigraph to different ends, consistent with their respective genres, all three attempted to correct some version of exclusionary politics. In particular, I sketch out a long tradition in which the epigraph has been used for highly gendered purposes, and explore how the practice laid the foundations for the modernist and, indeed, feminist, use of the fragment.